The Pathology of Salmonella Potsdam Infection in Yolk Membrane and Embryonated Chicken Eggs - Ramli, Zurina (2005)
Salmonellosis is a common and economically important disease in animal such as in poultry and a public health hazard to human.The aetiological agent involved was a Salmonella species. A new Salmonella serovar isolated in Malaysia, Salmonella potsdam (Salmonella enterica subsp. enterica serovar Potsdam) was isolated from a case of yolk sac infection in a young ostrich and believed to be pathogenic in young poultry chick and could be zoonotic to human.This salmonella serovar was inoculated into day-old chicks and embryonated chicken eggs, to study its pathogenicity and the pathological effects on yolk membrane. Day-old chicks were inoculated with S. potsdam using different routes, namely intraperitoneal(Group 1), oral (Group 2), subcutaneous (Group 3) and navel (Group 4). The mortality was 100%, 30%, 70% and 0% in each group respectively. Death occurred 2 days post-inoculation in Group 1, 8-11 days post-inoculation in Group 2 and 2-6 days post-inoculation in Group 3. The rapid death especially in Group 1 and the pathological changes in chicks which died shortly following inoculation with this pathogenic bacteria were considered to be indicative of shock and attributed to the action of endotoxin.The affected yolk membrane was mild to severely congested. The results from the bacteriological tests showed pure growth of this bacteria from the organs sampled, especially in Group 1.Most organs sampled from chicks that were euthanised after 14 days postinoculation, also revealed pure growth of S. potsdam. There was neither clinical sign nor mortality in chicks of group 4 which remained healthy like those in the control group. There was no bacteria isolated from chicks infected via the navel swab, which indicated that yolk sac infection by S. potsdam cannot occur from completely healed navel. Embryonated chicken eggs were infected with S.potsdam using different routes, namely through yolk sac (Group 1) and shell swab (Group 2).Salmonella potsdam appeared to be highly pathogenic to chick embryos in Group 1, with 100% mortality and 80% mortality in Group 2.The entire affected embryo in Group 1 showed congested yolk sac. Salmonella potsdam was recovered from all the embryos that died during the observation periods.Hatched chicks in Group 2 revealed pure growth of S. potsdam isolated from vital organs which cultured on Brilliant Green agar after placing in selenite broth indicative that these chicks could be carrier chicks.Salmonella potsdam was observed in the lesion of the yolk membrane.Its isolation from characteristic yolk membrane lesion indicated that it was associated with yolk sac infection.Immunohistochemistry observations validated the relationship between lesion seen in yolk membrane and S. potsdam. Immunoperoxidase staining technique facilitated detection and localisation of S. potsdam for light microscopy.Specific reactions were labeled in the yolk membrane. Salmonella potsdam antigen was observed in endodermal cells, around and in the blood vessels of the yolk membrane.This is the first report where the immunoperoxidase staining technique has been used in the study of yolk membrane lesions in day old chicks and embryonated chicken eggs.This study has revealed the pathogenesis of S. potsdam in chicks and embryonated chicken eggs